2011
DOI: 10.1177/1934578x1100600307
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Effects of the Major Quassinoids in a Standardized Eurycoma longifolia Extract (Fr 2) on the Bioavailability and Pharmacokinetic Properties, and their Implications for Oral Antimalarial Activity

Abstract: A simple validated LC-UV method for the phytochemical analysis of four bioactive quassinoids, 13α(21)-epoxyeurycomanone (EP), eurycomanone (EN), 13α,21-dihydroeurycomanone (ED) and eurycomanol (EL) in rat plasma following oral (200 mg/kg) and intravenous administration (10 mg/kg) of a standardized extract Fr 2 of Eurycoma longifolia Jack was developed for pharmacokinetic and bioavailability studies. The extract Fr 2 contained 4.0%, 18.5%, 0.7% and 9.5% of EP, EN, ED and EL, respectively. Following intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The findings of the fetal morphological, visceral and skeletal studies of the TAF273‐treated groups compared to those of the non‐treated control indicated a non‐teratogenic effect of TAF273 at 100 mg/kg dose level. Furthermore, the possible toxic accumulation of chemicals in the foetus (Eriksson et al ., ) may not arise since the bioavailability and absorption of the quassinoids from TAF273 were relatively low, due to their polarity, short half‐life and high elimination rate (Low et al ., ; Chan, )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the fetal morphological, visceral and skeletal studies of the TAF273‐treated groups compared to those of the non‐treated control indicated a non‐teratogenic effect of TAF273 at 100 mg/kg dose level. Furthermore, the possible toxic accumulation of chemicals in the foetus (Eriksson et al ., ) may not arise since the bioavailability and absorption of the quassinoids from TAF273 were relatively low, due to their polarity, short half‐life and high elimination rate (Low et al ., ; Chan, )…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the fetal morphological, visceral and skeletal studies of the TAF273-treated groups compared to those of the non-treated control indicated a non-teratogenic effect of TAF273 at 100 mg/kg dose level. Furthermore, the possible toxic accumulation of chemicals in the foetus (Eriksson et al, 1973) may not arise since the bioavailability and absorption of the quassinoids from TAF273 were relatively low, due to their polarity, short half-life and high elimination rate (Low et al, 2011;Chan, 2012) In conclusion, the no-observed adverse effect level (NOAEL) of TAF273 as observed from the reproductive toxicity and teratology studies in rats of both sexes was 100 mg/kg (equivalent to 32 mg/kg of total quassinoids). The dose was at least 10-and 20-fold lower than the acute lethal dose in female and male rats, respectively.…”
mentioning
confidence: 99%
“…The standardized quassinoids‐enriched fraction of EL from the root was prepared following the method established previously by Low, Das, and Chan (). SQEL contains 14.49 ± 0.26% of eurycomanone, 7.39 ± 0.17% epoxyeurycomanone, 0.72 ± 0.06% 13,21‐dihydroeurycomanone, and 9.54 ± 0.22% w /w eurycomanol (Al‐Salahi et al, ; Low, Teh, Yuen, & Chan, ). The pure compound, eurycomanone, was purchased, and its purity (>96%) was verified using HPLC (Chengdu Biopurify Phytochemicals Ltd., Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Eurycomanone is the most abundant phytochemical quassinoids in E. longifolia roots [24, 27 and 29] which has stable composition (not easily metabolized) [30]. A study by Low et al [31] reported that eurycomanone and 13α-(21)-epoxyeurycomanone possessed good physicochemical properties such as chemical stability, plasma stability, plasma protein binding, solubility and permeability. In fact, both of them are the main quassinoids contributing to the overall antimalarial activity of E. longifolia .…”
Section: Resultsmentioning
confidence: 99%